2013
DOI: 10.7314/apjcp.2013.14.9.5153
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Risk Factors for Thyroid Cancer: A Prospective Cohort Study in Khon Kaen, Thailand

Abstract: Background: Because of the gender disparity in the incidence of thyroid cancer, this study aimed to determine the association between reproductive factors and thyroid cancer. Methods: A total of 10,767 eligible women from the Khon Kaen Cohort, recruited and interviewed between 1990 and 2001, were followed up until 2011. The data were linked to the Khon Kaen Population-Based Cancer Registry to detect thyroid cancer cases. Results: There was 17 thyroid cancer cases detected, an incidence of 11.2 per 100,000 pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
3
15
1
Order By: Relevance
“…Despite two case-control studies performed in China (Preston-Martin et al, 1993) and New-Caledonia (Truong et al, 2005) evidenced, as we did, an increased risk in women who were everpregnant, two cohort studies, performed in China (Wong et al, 2006) and Japan (Pham et al, 2009), did not evidence such an increased risk, and another performed in Thailand, although based on 17 cases showed a decreased risk (Sungwalee et al, 2013). Results in other populations are heterogeneous (Peterson et al, 2012) and this heterogeneity does not seem to be attributable only to differences in number of children between studied populations.…”
Section: Discussioncontrasting
confidence: 79%
“…Despite two case-control studies performed in China (Preston-Martin et al, 1993) and New-Caledonia (Truong et al, 2005) evidenced, as we did, an increased risk in women who were everpregnant, two cohort studies, performed in China (Wong et al, 2006) and Japan (Pham et al, 2009), did not evidence such an increased risk, and another performed in Thailand, although based on 17 cases showed a decreased risk (Sungwalee et al, 2013). Results in other populations are heterogeneous (Peterson et al, 2012) and this heterogeneity does not seem to be attributable only to differences in number of children between studied populations.…”
Section: Discussioncontrasting
confidence: 79%
“…Concerning age at menarche and DTC risk, most studies reported no significant associations, whereas other showed either early (<12 years) (16, 20, 29) or late (>15–16 years) (13, 16, 18, 27) age at menarche to be weakly associated with increased DTC risk. A history of irregular menstrual cycles has been reported to confer a higher risk of DTC, the magnitude of the observed associations being generally weak and/or limited to specific subsets of population (18, 27).…”
Section: Resultsmentioning
confidence: 96%
“…Finally, 24 studies met the inclusion criteria, including 7 cohort studies [1214, 16, 17, 32, 33] and 17 case-control studies [1820, 34–47] (Supplementary Figure S1). The detailed characteristics of these studies were shown in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%